Primary Clear Cell Renal Cell Carcinoma with Marked Intraluminal Mucin Secretion - Oğuzhan OKCU; Kemal BEHZATOĞLU; Yasemin ÇAKIR; Esra PAŞAOĞLU; Uğur YÜCETAŞ (Federation of Turkish Pathology Societies, 2019)
Clear cell renal cell carcinoma with mucin secretion is an unexpected situation. Primary renal adenocarcinoma and various metastatic carcinomas should be considered in the differential diagnosis. Prognostic significance is not yet fully known due to the limited number of reported cases, and these lesions have been grouped under unclassified renal cell carcinoma. In our study, clear cell renal cell carcinoma with significant luminal mucin secretion is discussed with its histological, histochemical and immunohistochemical features.